A Facile, Efficient and Chemoseletive Deprotection of Silyl Ethers Using Zinc (II) Trifluoromethanesulfonate - Reddy, Kotthireddy T.; Sreenivasulu, Reddymasu; Veronica, Deekala; Chandrasekhar, Choragudi; Anitha, Kowthalam; Raju, Rudraraju Ramesh (Letters in Organic Chemistry, 2018)
Background: A number of protective groups for hydroxyl functional groups have been developed to date. Alcohols are most commonly protected as ethers and esters, where in alkyl and benzyl ethers are strong protective groups while others, like THP, TBS, TPS and MEM/MOM ethers are acid labile. Among all other hydroxyl protecting groups, Silyl ethers are the most frequently used protecting groups because they are easily and efficiently installed and are stable to a variety of useful reagents and reaction conditions. Among the silyl ethers, triethylsilyl (TES), tert-butyldimethylsilyl (TBDMS), triisopropylsilyl (TIPS), and tert-butyldiphenylsilyl (TBDPS) moieties are the frequently used hydroxyl protecting groups in multi step organic syntheses. Methods: A mild, efficient and selective method for the deprotection of variety of silyl ethers developed in high yields by using 20 mol % of Zinc (II) trifluoromethanesulfonate (Zn(OTf)2) at room temperature in methanol as a solvent without affecting both the acid and base sensitive protecting groups was reported. Results: To study the generality of this methodology, several silyl ethers were prepared from a variety of substrates having different protecting groups and subjected to desilylation using Zn(OTf)2 in MeOH. Conclusion: In conclusion, mild and efficient protocols for the deprotection of variety of silyl ethers using 20 mol % of Zn(OTf)2 at room temperature in MeOH have been established, in which both the acid and base sensitive groups are unaffected.
Keywords: RO-PMB